Intervención fisioterapéutica en pacientes post artroplastia de rodilla. - Ramírez Andy, Amy Mishell (2025)
Total knee arthroplasty has been consolidated as an effective surgical solution to treat degenerative joint pathologies such as osteoarthritis. However, this intervention success depends on a great extent of a proper rehabilitation process in which physiotherapy plays the core role. This study was aimed to analyze the postoperative physiotherapeutic intervention impact on the functional patient recovery undergoing to the total knee arthroplasty. This research accounts for a bibliographic, retrospective, descriptive and inductive study was carried out, the sample consisted of 25 randomized clinical trials, selected by means of a systematic search in scientific databases such as PubMed, PEDro, Scopus, Cochrane, among others, applying inclusion criteria and evaluating the methodological quality with the PEDro scale. The study findings showed that the post-surgical physical therapy significantly improved the joint range, muscle strength, gait and balance, reducing pain as well as increasing patient functionality. Among strategies used included progressive training, early mobilization, gait reeducation and self-care education. Therefore, it is concluded that the implementation of structured physiotherapeutic protocols favors an integral functional recovery, contributing to optimize the quality of life of the operated patient and to the success of the prosthesis placed.